PENGARUH WORK-LIFE BALANCE DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA PASCASARJANA UIN ALAUDDIN MAKASSAR - Danial, Danial; Badaruddin, Badaruddin; Nanda, Giri Dwi; Said, Muh; Abdullah, Abdullah (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze and examine the influence of work-life balance and work motivation on employee job satisfaction at the Postgraduate Program of UIN Alauddin Makassar. This research employs a quantitative approach with an ex-post facto method. The study's respondents consist of 32 employees, determined using a saturated sample technique. Data collection was conducted using a questionnaire distributed to all respondents. The data were analyzed using descriptive statistics through multiple linear regression analysis. The results of the study indicate that work-life balance has a positive effect on employee job satisfaction, although its influence is smaller compared to work motivation, which has been proven to have a stronger impact. The findings also show that work-life balance and work motivation simultaneously have a positive effect on employee job satisfaction at the Postgraduate Program of UIN Alauddin Makassar, even though job satisfaction itself is a multidimensional phenomenon influenced by many factors. Therefore, organizational strategies to enhance job satisfaction should adopt a holistic approach that considers work-life balance, motivational drives, and other supporting factors.